Chinese Nationalism Under Xi Jinping Revisited. (June 2019) - Bhattacharya, Abanti
In China, nationalism that took root in the era of globalization under the third-generation leadership of Jiang Zemin is principally meant to address the internal threats challenging party legitimacy and stability and not to resist the foreign enemies, as was the goal in the twentieth century. This is because internal stability is considered prerequisite to harness the potentials of globalization. Paradoxically therefore, nationalism and globalization, that are antithetical forces, go hand in hand in China. Under the current leadership, both the forces of nationalism and globalization are underscored in Xi Jinping's dream project- the Belt and Road Initiative (BRI). Notably, the success of BRI is contingent on the persistence of globalization externally. But the rising trends of de-globalization in the West do not augur well for the BRI that has been envisaged to not only meet the demands of a slowing economy but to expand China's global footprints, and thereby, fulfil the China Dream. Therefore, a sense of insecurity pervades Chinese nationalism. This 'insecure' nationalism under Xi Jinping is engendering a belligerent turn to Chinese foreign policy.